Management and outcome of primary CNS lymphoma in the modern era: An LOC network study. (10th March 2020) - Houillier, Caroline; Soussain, Carole; Ghesquières, Hervé; Soubeyran, Pierre; Chinot, Olivier; Taillandier, Luc; Lamy, Thierry; Choquet, Sylvain; Ahle, Guido; Damaj, Gandhi; Agapé, Philippe; Moluçon-Chabrot, Cécile; et al.
Abstract : Objective: Real-life studies on patients with primary CNS lymphoma (PCNSL) are scarce. Our objective was to analyze, in a nationwide population-based study, the current medical practice in the management of PCNSL. Methods: The French oculo-cerebral lymphoma network (LOC) database prospectively records all newly diagnosed PCNSL cases from 32 French centers. Data of patients diagnosed between 2011 and 2016 were retrospectively analyzed. Results: We identified 1, 002 immunocompetent patients (43% aged >70 years, median Karnofsky Performance Status [KPS] 60). First-line treatment was high-dose methotrexate-based chemotherapy in 92% of cases, with an increasing use of rituximab over time (66%). Patients <60 years of age received consolidation treatment in 77% of cases, consisting of whole-brain radiotherapy (WBRT) (54%) or high-dose chemotherapy with autologous stem cell transplantation (HCT-ASCT) (23%). Among patients >60 years of age, WBRT and HCT-ASCT consolidation were administered in only 9% and 2%, respectively. The complete response rate to initial chemotherapy was 50%. Median progression-free survival was 10.5 months. For relapse, second-line chemotherapy, HCT-ASCT, WBRT, and palliative care were offered to 55%, 17%, 10%, and 18% of patients, respectively. The median, 2-year, and 5-year overall survival was 25.3 months, 51%, and 38%, respectively (<60 years: not reached [NR], 70%, and 61%; >60 years: 15.4 months, 44%, and 28%). Age, KPS, sex, and response to induction CT were independent prognostic factors in multivariate analysis. Conclusions: Our study confirms the increasing proportion of elderly within the PCNSL population and shows comparable outcome in this population-based study with those reported by clinical trials, reflecting a notable application of recent PCNSL advances in treatment.